Enhancing the effectiveness of digital transformation on teaching in higher education in Kuwait - Alkandari, Fouad; Alsaber, Ahmad; Al-Kandari, Anwaar; Alboloushi, Bedour; AlMutairi, Shihanah (Frontiers in Education, 2024)
This study examines the digital citizenship behavior and behavioral intention of faculty members as mediators in the Public Authority for Applied Education and Training (PAAET) colleges to evaluate the effectiveness of using technology in teaching and to provide a case study of higher educational institutions in Kuwait. The paper provides theoretical insights and empirical support for the selective hypotheses about the four factors namely: performance expectancy (PE), effort expectancy (EE), social influence (SI) and facilitating conditions (FC) affecting the faculty members readiness (RED) through the mediation of both Behavioral Intention (BI) and Digital Citizenship Behaviour (DCB). The paper evaluates 28 hypotheses testing direct and indirect relationships of these variables. A survey of 122 faculty members from PAAET colleges in Kuwait has been conducted. The results provide valuable insights by confirming eight important paths of relationships, related to the inputs such as efforts, social influence, as well as performance as an output in determining the readiness. The study raises empirical doubts on the remaining 20 hypotheses, therefore, providing new evidence to reconsider the currently established relationships in the areas of technology acceptance and digital citizenship. Ultimately, this study contributes to the ongoing discussion on digital transformation in education by offering a broader perspective on faculty readiness. It provides a comprehensive understanding of key factors influencing the effective use of technology in the context of higher education institutions in Kuwait. The results offer valuable implications for policy and practice that can enhance technology use among faculty members.